The Effectiveness of Public Green Open Space Capabilities in Reducing Flooding - Yumna; Witno; Najib, Nardy Noerman; Faqi, Muh (Universitas Djuanda, 2024)
The Palopo City watershed could not accommodate the high discharge of rainfall that had fallen previously. The Green Open Space (GOS) had an ecological function by absorbing rainwater. Urban green open spaces absorbed surface flow water in the past, reducing the risk of flooding. In the past, this research measured the effectiveness of three green open spaces (Islamic Center, Pancasila Field, and Salubulo Field) in reducing flooding in Palopo City. We collected data on vegetation types, infiltration capacity, and runoff discharge. Data analysis involved the analysis of infiltration capacity (F), runoff discharge (Q), and green open space effectiveness. In the three green space locations, the following vegetation types were found: Katapang (Terminalia catappa), Palm (Dypsis lutescens), Trambesi (Samanea Saman), and Grass (Cyperus rotundus). The highest total infiltration capacity in the Salubulo Field Green Space resulted in 155 m3/hour (fast category). In the past, the most significant runoff discharge's total value was GOS Pancasila Field: 713.4 mm3/minute. The study concluded that the Salubulo Field Green Space had the highest infiltration capacity (160 m3/hour) and runoff discharge (69 mm3/minute), making it the most effective in reducing flooding in Palopo City in the past. This was > 1 (effectiveness criteria achieved), and the space was dominated by vegetation (trees and grasses).